The prevalence of lactic acid bacteria as probiotic in Malaysian fermented food products: A review / Norsyafiqka Kamsan and Nur Rabiatul Adawiah Mohammad Noor - Kamsan, Norsyafiqka; Mohammad Noor, Nur Rabiatul Adawiah (2021)
Ingestion of probiotics products have been associated with a variety of health advantages and are beneficial to the gut. The most common types of probiotics employed for their beneficial properties are lactic acid bacteria (LAB) which are typically found in fermented food. In Malaysian fermented foods, LAB is already being used especially in non-dairy fermented foods. However, these fermented food products are usually prepared on a small scale which might be exposed to microbial contamination. Numerous research has been conducted to isolate LAB from several varieties of Malaysian fermented food in order to find the ideal strain to use as starter culture. Hence, the review of LAB in Malaysian fermented food products was conducted to identify which fermented food products can be classified as probiotic. For this, studies published and indexed in Google scholar between 2016-2020 were manually searched and analysed. The study includes products from different food groups which are fish, seafood, legumes, vegetables and fruits. This review also highlights the parameter of probiotics screening and the benefits of probiotics in fermented food. Malaysian fermented food products were identified to be a good potential probiotics property with Lactobacillus spp. was found in most of the fermented products. Lactobacillus spp. can survive the human digestive tract and shows antimicrobial effects towards pathogenic bacteria. Hence, Malaysian fermented foods that are cheap and abundant may be a good alternative for foods with potential probiotics and thus can be considered as functional foods.